Building Physics, Design, and the Collaborative Build: Sustainability and Resilience in Architectural Education. (3rd January 2018) - Stieldorf, Karin
Abstract : The earlier architectural students are encouraged to actively engage with environmental issues, the more likely they are to consider them as key in later professional practice. To this end, Vienna University of Technology (TU Wien) has for over two decades been running courses which involve students in projects focused around the model of collaborative design‐build competitions that address such issues. Associate ProfessorKarin Stieldorf, a co‐founder of the university's Sustainable Building and Design Group, describes some of these initiatives – notably including her team's winning entry for the US Department of Energy's 2013 Solar Decathlon competition.